The kalaṅkyaṅ in Old Javanese literature: from bird of prey to mirror image of the poet - Jákl, Jiří (Bijdragen tot de taal-, land- en volkenkunde, 2022)
Abstract The article discusses an enigmatic Old Javanese bird named kalaṅkyaṅ. The avian species known by this name is identified as the white-bellied sea eagle, a bird common in the past in the coastal parts of Java. In the second section it is argued that the kalaṅkyaṅ bird is represented in Old Javanese poetry as the mirror image of the Javanese kawi (poet).
Gesehen am 25.10.2022